2015
DOI: 10.1002/ppap.201500007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DBD Inlet Geometry on the Homogeneity of Plasma‐Polymerized Acrylic Acid Films: The Use of a Microplasma–Electrode Inlet Configuration

Abstract: Multiple vapor inlet systems have been developed to enhance the homogeneity of deposited polyacrylic acid films via medium and atmospheric pressure plasma technology. Different inlet systems were experimentally tested and optical reflectance spectrometry (OPS) was used to measure the differences in thickness of the films along the exposed surface. Standard deviations of more than 65% were reduced to less than 10%. COMSOL models point to the gas flow as the main contributor to the film homogeneity. OPS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…Even if DBD reactors have been previously shown to possibly result in the deposition of scarcely homogeneous pPAA coatings, [14] it was recently demonstrated that this problem can be overcome by optimizing the design of the precursor inlet systems. [15] On the other hand, results of previous works on pPAA deposition [16][17][18] showed that in the AP-DBD system the effect of monomer fragmentation on the retention of -COOH groups turns out to be relevant: the higher the monomer fragmentation, the lower the amount of -COOH groups on the coated substrate, [16,19] as also experimentally evidenced by Palumbo et al [19] through a correlation of optical emission spectroscopy and X-ray photoelectron spectroscopy results.…”
Section: Introductionmentioning
confidence: 79%
“…Even if DBD reactors have been previously shown to possibly result in the deposition of scarcely homogeneous pPAA coatings, [14] it was recently demonstrated that this problem can be overcome by optimizing the design of the precursor inlet systems. [15] On the other hand, results of previous works on pPAA deposition [16][17][18] showed that in the AP-DBD system the effect of monomer fragmentation on the retention of -COOH groups turns out to be relevant: the higher the monomer fragmentation, the lower the amount of -COOH groups on the coated substrate, [16,19] as also experimentally evidenced by Palumbo et al [19] through a correlation of optical emission spectroscopy and X-ray photoelectron spectroscopy results.…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, information on the distribution of the monomer in the volume close to the substrate was also able assist in evaluating the thin film growth during the deposition process. For example, it has already been shown that the gas velocity and mass fraction can be correlated to the deposition pattern on a substrate [39] and the plasma behavior [35]. In the latter study it was also revealed that placing an additional plate at the edge of the plasma jet capillary intensified the gas purity near the surface when working with a small gap distance to the substrate [35].…”
Section: Cfd Simulationsmentioning
confidence: 90%
“…A DBD parallel plate set-up, with helium as carrier gas, will be used in this work since this reactor set-up has already been thoroughly studied and is proven to be very successful for several applications, including the deposition of coatings [13,34,35]. …”
Section: Accepted Manuscriptmentioning
confidence: 99%